Analysis of Employees Performance in Karangkidul Village Central Semarang Distric Semarang City - Atkawidyarso, Dwi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2012)
This study aims to describe and analyze the performance of employees Karangkidul Village Central Semarang District and look at the factors that hinder the performance of the employee. The research approach using qualitative approaches. Research activities carried out by the activities of collecting, describing and interpreting data on the situation experienced, activities, views, attitudes or trends indicated that apparent in the performance that is being run. Data collection is done by in-depth interviews and documentation.Survey results revealed the performance of employees in the Karangkidul Village seen from the indicator reliability, access, staff communication, honesty, decency, security services, employee knowledge and direct evidence has been good in providing services while the other two indicators, namely responsiveness and competence of employees, including less well. The factors that hinder the performance of employees is the lack of socialization procedures effectively to the public services, lack of legal certainty to the employee who commits an offense and limited infrastructure and capacity utilization and access to information technologies that are less optimal by the employee.Suggestions related to the results of the study researchers gave them to improve employee responsiveness indicators it is necessary to Standard Operating Procedures of community service. To improve employee competency indicators leaders can develop employee development program. To avoid the impression of a complicated administrative and bureaucratic, and boards can use online Standard Operating Procedures information society services. Leaders must enforce discipline an employee working in a professional manner. Improved working facilities is absolutely necessary in order to improve employee performa